Cold light of day [large type] - Goddard, Elizabeth (Goddard, Elizabeth. Missing in Alaska, 2023)
"Police Chief Autumn Long is fighting to keep her job in the quiet Alaska town of Shadow Gap when an unexpected string of criminal activity leaves her with a wounded officer, unexplained murders, and an attack on her own father. Despite her mistrust of outsiders, she turns to Grier Brenner, a newcomer who seems to have the skills and training Autumn needs to face this threat to her community. Grier is in Alaska for the same reason many others are -- to disappear -- when Chief Long enlists his help. He emerges from the shadows and proves his mettle, but his presence in her life could be a deadly trap for them both. If his secret is exposed, all will be lost. And he's not sure even Autumn could save him."--